The relationship between test-anxiety and academic achievement among Iranian adolescents - Yousefi, Fayegh; Abu Talib, Mansor; Mansor, Mariani; Juhari, Rumaya; Redzuan, Ma'rof (Canadian Center of Science and Education, 2010)
The purpose of this study is to determine the relationship between test-anxiety and academic achievement among adolescents in Sanandaj, Iran. The respondents comprised of 400 students (200 boys and 200 girls) in the age range of 15-19 years old that were randomly selected from nine high schools in Sanandaj, Iran. A self administered questionnaire was used for data collection which includes a Test-Anxiety Inventory (TAI) (Abbolghasemi, 1988), Grade Point Average (GPA) score and personal information. Result shows that there is a significant correlation (r= -0.23, p=.000) between test anxiety and academic achievement among adolescents. In addition, there is a significant difference (t= 5.47, p=.000) of academic achievement between male and female adolescents whereby female score higher in their academic achievement. It is recommended that academic achievement and mental health be improved in school settings with support strategies such as educational guidance, counseling and psychotherapy or other psycho-educational program such as teaching life skill.